2023
DOI: 10.1093/ijnp/pyad050
|View full text |Cite
|
Sign up to set email alerts
|

(S)-Ketamine but Not (R)-Ketamine Shows Acute Effects on Depression-Like Behavior and Sleep-Wake Architecture in Rats

Abstract: Background Racemic ketamine consists of two enantiomers, namely (R)ketamine and (S)ketamine, with distinguishable pharmacological properties. Both enantiomers have been reported to show rapid antidepressant effects in rodents. Currently, the (S)enantiomer has been approved for the treatment of major depression, while (R)ketamine failed to show antidepressant effect in recent clinical studies. Major depressive disorder is frequently characterized by disinhibition of rapid eye movement (REM) sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Recently, we have shown that 15 mg/kg i.p. (S)-ketamine but not (R)-ketamine has acute effects on depression-like behavior and sleep–wake architecture, which is in line with the clinical data [ 6 ]. To elaborate, (S)-ketamine decreased REM sleep time at two and three hours following administration, while it decreased NREM sleep and increased wakefulness in the first two hours.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…Recently, we have shown that 15 mg/kg i.p. (S)-ketamine but not (R)-ketamine has acute effects on depression-like behavior and sleep–wake architecture, which is in line with the clinical data [ 6 ]. To elaborate, (S)-ketamine decreased REM sleep time at two and three hours following administration, while it decreased NREM sleep and increased wakefulness in the first two hours.…”
Section: Introductionsupporting
confidence: 82%
“…Standard rodent food and tap water were available ad libitum for the animals during the whole study. The sample size (6–8 rats/group) was determined based on previous research investigating the sleep effect of conventional antidepressants and ketamine enantiomers [ 6 , 14 , 15 , 28 ]. Before surgery, the rats were acclimatized to the housing conditions for 7 days and were handled for 2 min each day for 5 days during this period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some limitations existed here, as long-term cocaine exposure, despite no effects on “inactive” lever presses, might have affected the baseline activity of the rats. The inhibitory action of esketamine in a lower (5 mg/kg), but not higher (10 mg/kg), dose was unexpected, even more so that some locomotor inhibitory effects were noticed for esketamine doses (15 mg/kg) in the vehicle-pretreated rats, but not repeatedly adrenocorticotropic-hormone (ACTH)-treated rats [ 23 ], while other authors recently demonstrated a lack of motor effects of esketamine in a dose range of 15–20 mg/kg in rats [ 30 , 31 ]. Although a significant effect, the number of inactive lever presses following the 5 mg of esketamine was similar to the response during the cocaine self-administration or vehicle-pretreated rats during the cocaine reinstatement test in rats forwarded to abstinence with social isolation.…”
Section: Discussionmentioning
confidence: 99%